THE INFLUENCE OF ANIMATION VIDEO MEDIA ON ABILITY EARLY CHILD RHYTHMAL GYMNASTICS At Eria Kindergarten: PENGARUH MEDIA VIDIO ANIMASI TERHADAP KEMAMPUAN SENAM IRAMA ANAK USIA DINI Di TK Eria - Supriyani Siregar, Epi; Priono, Joko; imanuddin; Aminah, Siti; Harianti, Puji (LPPM UPMI, 2023)
This study aims to The research method used in this research is quantitative research (experimental), with the type of one-group pretest-posttest design. With the aim of knowing the effect of the use of animation media on the ability of early childhood rhythmic gymnastics. This research was conducted at Eria Kindergarten with the address Jalan Karya Jaya, Medan Johor District. The time for the research to be carried out is in the even semester of the 2021/2022 school year, starting from June 6 to June 22, 2022. The population in this study were 35 children in group B. The results of the research on the influence of Video Animation Media to increase the scientific abilities of group B children were carried out in the data comparison stage before being given Video Animation Media (pre-test) and after being given Video Animation Media (post-test). tests). This was carried out in 6 meetings with the first meeting being an introduction and the second meeting explaining the material properties of water and providing activities based on group B children's rhythmic gymnastics, then conducting initial observations to collect data before conducting Video Animation Media and after being given Video Animation Media with assessment instruments that have been provided. Based on the calculation of the hypothesis test above, it can be seen that the tcount = 4.914 and because dk = n-1 then dk = 15-1 = 14 and the real level = 0.05 so that the ttable is 1.761. It can be concluded that tcount > ttable = 4.914 > 1.761 thus Ho is rejected and Ha is accepted with it being stated that there is a significant influence on the use of animated video media on the ability of early childhood rhythmic gymnastics in the Medan Johor sub-district for the 2021/2022 Academic Year.